Strengthening Student Citizenship Literacy in the Digital Era through Pancasila Education - Tri Indrayati; Uky Eji Anggara; Wilda Afriani; Khoerotun Nisa Liswati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The rapid development of digital technology has significantly transformed patterns of communication, information access, and civic participation, while simultaneously presenting new challenges to strengthening university students' civic literacy. This study aims to analyze and synthesize previous research on the role of Pancasila Education in strengthening students' civic literacy in the digital era. The study employed a literature review method by examining relevant national and international scholarly publications published between 2020 and 2026. Data were analyzed using qualitative content analysis through the processes of identification, classification, interpretation, and synthesis of research findings. The results indicate that the major challenges to students' civic literacy include the spread of misinformation, limited critical thinking skills, weak digital ethics, and increasing polarization in digital spaces. Pancasila Education plays a strategic role in strengthening civic knowledge, civic skills, and civic dispositions through the internalization of Pancasila values integrated with contextual learning, discussions of contemporary issues, collaborative learning, project-based learning, and the promotion of digital citizenship. This review concludes that strengthening civic literacy requires the transformation of Pancasila Education into a more adaptive and innovative learning approach that responds to technological developments while fostering critical, democratic, responsible, and value-oriented citizens